Knowledge Regarding Post-Exposure Prophylaxis Of Hiv/Aids Infection And Perceived Threat Due To Needle Stick Injury Among Nursing Students Of Selected Nursing College At Jaipur ( Raj - Ashok Yadav; Subhash Sharma; Sanju Kumari (International Journal of Medical Research and Review, 2022)
Introduction: Needle stick injuries (NSI) has always been one of most important risk factors forhealthcare workers (HCWs) for transmission of various infections such as hepatitis B, hepatitis C andhuman immunodeficiency virus (HIV). As per 2008-2009 HIV estimates, there are an estimated 23.9lack people currently living with HIV/AIDS in India with an adult prevalence of 0.31% in 2009.Material and methods: It is a descriptive non-experimental study carried out among nursingstudents studying at teaching institutes in Jaipur city (Rajasthan). A study was conducted duringyear 2020 and 92 Bsc nursing students were selected by using total enumerative sampling techniquerespectively. The reliability of knowledge tool was conducted through Kuder and Richardson Formula20 (KR20) result was 0.84 and reliability of 5 point rating scale was analyzed by using Cronbach Alfamethod it was 0.92.Result: The level of knowledge of nursing students, in which (18) 22.5% hadpoor knowledge, (50) 62.50% had average knowledge and (12) 15% of them had good knowledgeregarding post-exposure of prophylaxis of HIV/AIDS infection. The level of perceived threat ofnursing students, in which (62) 77.5% had high level perceived threat, (17) 21.25% had moderatelevel perceived threat and (1) 1.25% of them had low level perceived threat due to needle stickinjury. It evidenced that for correlation between knowledge and level of perceived threat calculatedvalue of Karl Pearson's correlation coefficient is 0.76 and tabulated value of correlation coefficient is0.250 for df 78 at 0.05 level of significance.Conclusion: The present study reveals that majority ofnursing students had average knowledge regarding post-exposure prophylaxis of HIV/AIDS infectionand low level perceived threat due to needle stick injury.